Synthesis, Crystal Structure, Electronic Structure, and Catalytic Properties of Ni3GaSb. Issue 14 (26th March 2021) - Roy, Nilanjan; Kumari, Saroj; Sikdar, Ritobroto; Sharma, Anjali; Harshit,; Ghanta, Sivaprasad; Sharma, Sudhanshu; Deshpande, Parag A.; Jana, Partha P.
Abstract: Single crystalline titled phase is synthesized by conventional high‐temperature solid‐state synthesis. Crystal structure of Ni3 GaSb is re‐investigated by single‐crystal X‐ray diffraction and energy dispersive X‐ray analysis. The compound crystallizes in P 63 / mmc space group, the structure can be described as an intermediate of NiSb and Ni2 In structures, similar to Ni3 GaAs. Electronic structure of the compound is investigated by first‐principles electronic structure calculations on the ordered model of Ni3 GaSb. Stability and bond analysis was done by COHP calculations. Hetero‐atomic Ni−Sb and Ni−Ga interactions play a major role towards to stability of the compound, these interactions are also responsible to modify the electronic structure of the titled compound. It was tested for catalytic activity and selectivity for acetylene hydrogenation reaction. Ni3 GaSb was found to be a selective catalyst with 95.53 % C2 H2 conversion giving 60 % selectivity towards C2 H4 at 550 °C. Abstract : Single‐crystalline Ni3 GaSb was synthesized by high‐temperature solid‐state synthesis. The compound crystallizes in the P 63 / mmc space group, an intermediate of NiSb and Ni2 In structures, like Ni3 GaAs. In a poor metallic framework, Ni−Sb and Ni−Ga interactions play a major role for the stability of the compound. For acetylene semi‐hydrogenation, Ni3 GaSb was found to be a selective catalyst with 95.53 % C2 H2 conversion and 60 % selectivity towards C2 H4 at 550 °C.